PENGAMBILAN ZAT WARNA ALAMI ANTHOSIANIN DARI EKSTRAKSI KULIT MANGGIS (Garnicia mangostana L) - Murni Yuniwati; Fransiska Ovitasari; Dewi Wulandari (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2013)
Mangosteen is a fruit that is very popular in Indonesia. Besides delicious taste, mangosteen also has many benefits and efficacy, including the skin of the fruit. Skin tannin mangosteen contains compounds that can be used in the leather tanning industry, xanthone antioxidants, and anthosianin as a natural dye. Anthosianin in mangosteen skin, can be taken through the process of using solvent extraction and performed in acidic conditions. In this study, the solvent used is etanol and 2N HCl added as much as 0.1% by volume of etanol. The process carried out in a three-neck flask equipped with a heater, stirrer, and cooller. By using raw materials mangosteen peel 5 gams, 100 mL of etanol, and 0.1 mL of 2N HCl, the optimum process conditions obtained by using 3.5 hours, 60 ° C, the solvent content of 96% etanol and stirring speed 300 rpm. Under these conditions obtained anthosianin extracted total of 14.3275 mg.